Functional Marker Assisted Improvement of Stable Cytoplasmic Male Sterile Lines of Rice for Bacterial Blight Resistance - Ramalingam, Jegadeesan; Savitha, Palanisamy; Alagarasan, Ganesh; Saraswathi, Ramasamy; Chandrababu, Ranganathan (Frontiers in Plant Science, 2017)
Bacterial blight (BB), caused by Xanthomonas oryzae pv. oryzae is one among the major diseases in rice, which in severe condition cause losses up to 60 per cent in total yield. Marker assisted pyramiding of three broad spectrum BB resistance genes (xa5, xa13 and Xa21) in prominent rice varieties is the most economical and effective strategy for the management of the BB disease. We report here the pyramiding of three genes (xa5, xa13 and Xa21) in maintainer lines (CO 2B, CO 23B and CO 24B) of three promising wild abortive cytoplasmic male sterile lines (CO 2A, CO 23A and CO 24A) through functional markers assisted back cross breeding. IRBB60 with xa5, xa13 and Xa21 genes is used as a donor parent. BC2F1 and BC2F2 generations from a cross of CO 2B, CO 23B and CO 24B with IRBB60 were evaluated for bacterial blight and non-fertility restoration. In BC2F1, plants with all three resistance genes (xa5, xa13 and Xa21) and high parent genome recovery was identified. In BC2F2, plants with all resistance genes and without fertility restorer (Rf3 and Rf4) were selected. Based on agronomic traits, BB resistance and maintenance of sterility, two plants each in CO 2B x IRBB60, CO 24B x IRBB60 and one plant in CO 23B x IRBB60 combinations were identified. The identified lines were crossed with respective male sterile lines for conversion of improved B line into CMS line through back-crossing, in addition to selfing. The plants with high recurrent genome and phenotypically similar to parental lines and sterile are being used for the hybrid rice development program. Currently, using these lines (improved CMS line), test crosses were made to develop new rice hybrids. Hybrids combinations viz., CO 23A x AD08009R and CO 24A x IET20898R were found to be stable at different locations with high yield. The R line used in this study has been introgressed with xa5, xa13 and Xa21 genes in a separate breeding program. These new hybrids with resistance against bacterial blight will increase the crop production at BB environment.